Sanksi Pidana terhadap Pelaku Tindak Pidana Informasi dan Transaksi Elektronik - Komang Gede Dicki Saputra; I Made Sepud; Diah Gayatri Sudibya (Jurnal Konstruksi Hukum, 2021)
The internet is one of the electronic media in the field of information and communication that is able to connect people around the world, so that the world feels increasingly narrow and borderless because of the ease in establishing communication. Indonesia is currently experiencing a serious problem, namely that the people are no longer obedient to the law, even some of them are blind about the law not because they do not understand the law. Therefore it is important to socialize to the community. This study aims to explain criminal acts against the treatment of broadcasting information through social media as well as a solution to avoiding unfair treatment through social media. This research is designed to use normative legal research, which is looking for and sorting information obtained in the library without deviating from the issues discussed and the current positive law. The approach used is the statutory approach. Sources of research data are primary and secondary data. The results of the research show that the actions of a person who deliberately defames someone's name, whether it is done intentionally or not in public or on social media, can be sentenced to prison and compensation for the actions he has committed which the two Governments as guarantor of defamation victims do not remain silent other than Providing dependents to the victim also provides compensation in kind in the form of rules that prohibit someone from damaging the good name of Article 37 Paragraph (3) of the ITE Law as a solution for the government to reduce criminal acts of defamation and is a reference for judges in deciding matters related to defamation that's happening on social media.